2006
DOI: 10.1177/107110070602700904
|View full text |Cite
|
Sign up to set email alerts
|

Technique and Results of Achilles Tendon Detachment and Reconstruction for Insertional Achilles Tendinosis

Abstract: Background: Insertional Achilles tendinosis is a clinical entity that commonly occurs with other posterior heel disorders such as retrocalcaneal bursitis, Haglund deformity, intratendinous ossification and pretendinous bursitis. Complete detachment and reconstruction of the Achilles tendon was evaluated as a method of treatment for this condition. Methods: Seventyfive patients (81 heels) were treated over a 5-year period for chronic insertional Achilles tendinosis. These were divided in two groups: a nondetach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
118
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(122 citation statements)
references
References 3 publications
1
118
0
3
Order By: Relevance
“…Overall, the complication rates throughout the published studies of this procedure have varied from 4.7% to 41% (16). Some investigators have suggested that the most common reason for postoperative Achilles avulsion, and ultimately, reoperation is due to falls (13,14,17). In our retrospective study, we saw only 4.0% (4 of 99) of insertional Achilles repeat ruptures, and of these, 3 (75.0%) of the 4 had resulted from falls in the early postoperative period.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Overall, the complication rates throughout the published studies of this procedure have varied from 4.7% to 41% (16). Some investigators have suggested that the most common reason for postoperative Achilles avulsion, and ultimately, reoperation is due to falls (13,14,17). In our retrospective study, we saw only 4.0% (4 of 99) of insertional Achilles repeat ruptures, and of these, 3 (75.0%) of the 4 had resulted from falls in the early postoperative period.…”
Section: Discussionmentioning
confidence: 96%
“…Wagner et al (13) described a slightly more medial incision, comparing partial detachment and complete Achilles detachment for retrocalcaneal decompression, along with a proximal V-Y aponeurotic lengthening. In their retrospective analysis, 75 patients were divided into 2 groups, 26 and 49, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies evaluate various forms of surgery to treat Achilles tendinopathy [92,102,109,122,139,151,191]. The approaches vary greatly between studies based partly on the extent of abnormality.…”
Section: Surgerymentioning
confidence: 99%
“…Additional clinical trials are needed to confirm the effectiveness of recession alone. However, few studies have compared the method of reattachment or fixation of the Achilles tendon, and present practice has left this decision to the discretion of the surgeon (4,6).…”
mentioning
confidence: 98%